2017
DOI: 10.21566/tarbitderg.359162
|View full text |Cite
|
Sign up to set email alerts
|

Biplot Analiz Yöntemi ile Bazı Makarnalık Buğday Hatlarının Verim ve Kalite Özelliklerinin Değerlendirilmesi

Abstract: yetiştirme sezonlarında Diyarbakır'da yürütülmüş olup, verim ve kalite özellikleri üstün makarnalık buğday hatlarının belirlenmesi amaçlanmıştır. Araştırmada beş kontrol çeşit ve 20 hat materyal olarak kullanılmıştır. Deneme, tesadüf blokları deneme desenine göre dört tekerrürlü olarak kurulmuş ve tane verimi, hektolitre ağırlığı, bin tane ağırlığı, protein içeriği, irmik rengi ve SDS değeri incelenmiştir. Bileşik analiz sonucunda, genotip, yıl ve genotip x yıl interaksiyonlarında tüm özellikler yönünden öneml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The GGE biplot has been used in only a few studies to analyze the MET data of durum wheat in Turkey (Tekdal et al, 2017;Kendal, 2019). In our research, E contributed 83% of the total variation in the data, whereas G and GEI contributed less.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GGE biplot has been used in only a few studies to analyze the MET data of durum wheat in Turkey (Tekdal et al, 2017;Kendal, 2019). In our research, E contributed 83% of the total variation in the data, whereas G and GEI contributed less.…”
Section: Discussionmentioning
confidence: 99%
“…However, little attention is given to the interaction of genotypes with unpredictable target environments. In this context, METs can help understand genotypes' performance in various environments by measuring the stability of genotypes (Gs) across environments (Es) (Tekdal et al, 2017;Scapim et al, 2000). But, MET data are rarely used to their full potential, even though data on most plant traits have been collected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Güngör and Akgöl, (2015) and Bilgin et al, (2008) revealed that a high significant correlation of 1000 grain weight with grain yield implies that 1000 grain weight plays a very important role in the possible increase of the grain yield of new wheat genotypes in the Thrace Region. Öztürk and Korkut, (2017) and Tekdal et al, (2014) reported that TKW and TW had a positive effect on grain yield. The higher grain yields were found in examined varieties with the higher 1000-grain weight.…”
Section: Resultsmentioning
confidence: 98%
“…Ayrıca Kanat [14]' yaptığı araştırmada 444,7-597,0 kg/da, diğer bir çalışmada 522,35-654,33 kg/da, aralığında değiştiğini bildirmektedirler [29]. Tane verimi daha çok genotiplerin genetik özelliğinden ve çevrenin etkisinden etkilendiği araştırıcılar tarafından bildirilmiştir [30].…”
Section: Verilerin Değerlendirilmesiunclassified